The investigation of the association of alleles and genotypes of the polymorphic marker T786C of the eNOS gene at various stages of primary open-angle glaucoma - T. V. Gavrilova; A. R. Kinkulkina; A. S. Avagyan; O. A. Svitich (Российский офтальмологический журнал, 2024)
Purpose: to study the association of the polymorphic marker T786C of the eNOS gene with various stages of primary open-angle glaucoma (POAG).Materials and methods. Peripheral blood of 90 patients aged 56 to 89 yrs (ave. 71 yrs) with POAG stages I, II, III was tested. DNA was isolated using a set of ribosorbents (Synthol company); subsequently, a real-time PCR reaction was performed on a DT-96 amplifier using the set to determine the polymorphic marker T786C in the eNOS gene.Results. For all groups of patients, the frequency of occurrence of alleles and genotypes was calculated, and the relationship between the emergence of POAG and the presence of an unfavorable polymorphic marker was determined. The main changes were revealed at POAG stages II and III, whilst at stage I no effect of polymorphism T786C of the eNOS gene was observed.Conclusion. For the first time, a comparative assessment was made of the distribution of alleles and genotypes by the polymorphic marker T786C in the eNOS gene of patients with various POAG stages.